Analysis of sexual harassment instruments by Rasch Modeling to identify sexual harassers - Erwinda, Lira; Nirwana, Herman; Afdal, Afdal (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2020)
Sexual harassment is an issue that has attracted much attention in both children and adults. However, the victims often prefer to be silent on the matter for several reasons, even though it may have long term effects on them. Thevictims of sexual harassment need to be educated to increase awareness of the associated risks. To realize this goal, the perpetrators of this vile needs to be identified first, though this requires valid and reliable instruments. Thereis a sexual harassment instrument that facilitates the identification of the perpetrators. This instrument includes eight indicators with 32 items. Thehe results of testing the validity and reliability of the instrument with RASCH modeling shows that it meets the requirements and therefore it can be used to identify perpetrators of sexual harassment in Vocational High school.